Grading of hydrophobicity tests for virulence determination of Staphylococcus epidermidis of animal origin - DAS, S C (The Indian Journal of Animal Sciences, 2011)
The present communication reports the comparison of tests, viz. salt aggregation test (SAT), n-hexadecane adherence assay (HAA), xylene adherence assay (XAA) for measuring hydrophobicity - a virulence determinant of Staphylococcus epidennidis from healthy and clinically sick aniInals. Of the total 119 Staphylococcus epidennidis strains [cow raw milk (28); udder surface (30); chicken nose swab (24); pre-operative dog skin (27) and operated dog blood (10) salnples] tested; 35 (29.4%) could be detected as hydrophobic in HAA followed by 32 (26.9%) and 13 (11 %) in XAA and SAT, respectively. Analysis of the data revealed that, barring negligible difference, the efficacy of the HAA and XAA were equal and either test may be adopted for screening the pathogenic (hydrophobic) strains of S. epidernzidis of animal origin. Â